A reverse chemical ecology approach to explore wood natural durability. Issue 5 (25th March 2020) - Thomas, Perrot; Guillaume, Salzet; Nadine, Amusant; Jacques, Beauchene; Philippe, Gérardin; Stéphane, Dumarçay; Rodnay, Sormani; Mélanie, Morel‐Rouhier; Eric, Gelhaye
Summary: The natural durability of wood species, defined as their inherent resistance to wood‐destroying agents, is a complex phenomenon depending on many biotic and abiotic factors. Besides the presence of recalcitrant polymers, the presence of compounds with antimicrobial properties is known to be important to explain wood durability. Based on the advancement in our understanding of fungal detoxification systems, a reverse chemical ecology approach was proposed to explore wood natural durability using fungal glutathione transferases. A set of six glutathione transferases from the white‐rot Trametes versicolor were used as targets to test wood extracts from seventeen French Guiana neotropical species. Fluorescent thermal shift assays quantified interactions between fungal glutathione transferases and these extracts. From these data, a model combining this approach and wood density significantly predicts the wood natural durability of the species tested previously using long‐term soil bed tests. Overall, our findings confirm that detoxification systems could be used to explore the chemical environment encountered by wood‐decaying fungi and also wood natural durability. Abstract : Fungal detoxification systems could be used to explore the chemical environment encountered by wood decaying fungi and also wood natural durability.